Inactivation combined with cell lysis of Pseudomonas putida using a low pressure carbon dioxide microbubble technology. Issue 8 (12th May 2017) - Mulakhudair, Ali R; Al‐Mashhadani, Mahmood; Hanotu, James; Zimmerman, William
Abstract: BACKGROUND: Inactivation processes can be classified into non‐thermal inactivation methods such as ethylene oxide and γ‐radiation, and thermal methods such as autoclaving. The ability of carbon dioxide enriched microbubbles to inactivate Pseudomonas putida suspended in physiological saline, as a non‐thermal sterilisation method, was investigated in this study with many operational advantages over both traditional thermal and non‐thermal sterilisation methods. RESULTS: Introducing carbon dioxide enriched microbubbles can achieve ∼2‐Log reduction in the bacterial population after 90 min of treatment, addition of ethanol to the inactivation solution further enhanced the inactivation process to achieve 3, 2.5 and 3.5‐Log reduction for 2%, 5% and 10 %( v/v) ethanol, respectively. A range of morphological changes was observed on Pseudomonas cells after each treatment, and these changes extended from changing cell shape from rod shape to coccus shape to severe lesions and cell death. Pseudomonas putida KT 2440 was used as a model of gram‐negative bacteria. CONCLUSION: Using CO2 enriched microbubbles technology has many advantages such as efficient energy consumption (no heat source), avoidance of toxic and corrosive reagents, and in situ treatment. In addition, many findings from this study could apply to other gram‐negative bacteria. © 2017 The Authors. Journal of Chemical Technology & Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.